Sosialisasi Penerapan Kesehatan dan Keselamatan Kerja (K3) dalam Proyek Pembangunan Gedung RSIA Norfa Husada - Adeswastoto, Hanantatur; Desrimon, Arfi; Febryanto; Saputra, M. Azlan; Tasya; Nisa, Khoirun; Maulana Ar-Rahman, Anang (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
Community Service is one part of the Tri Dharma of Higher Education, which aims to make a real contribution to society. In the RSIA Norfa Husada Building construction project in Bangkinang District, this activity focuses on socializing the implementation of Occupational Safety and Health (K3). In construction projects, implementing K3 is very important to reduce the risk of work accidents, increase worker awareness about work safety, and ensure a safer and more comfortable workplace. This program aims to increase workers' understanding of work safety standards through outreach, installing K3 signs, and evaluating the safety management system in the project. The methods used include educational, technical and participatory approaches by providing regular training, ensuring compliance with the use of personal protective equipment (PPE), and conducting regular safety inspections. The results of this activity show that workers are more aware of the importance of implementing K3.